2003
DOI: 10.1002/ijc.11432
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between genetic polymorphism of cytochrome P450‐1B1, sulfotransferase 1A1, catechol‐o‐methyltransferase and tobacco exposure in breast cancer risk

Abstract: Genetic polymorphisms of enzymes involved in the metabolism of xenobiotics and estrogens might play a role in breast carcinogenesis related to environmental exposures. In a case-only study on 282 women with breast cancer, we studied the interaction effects (ORi) between smoking habits and the gene polymorphisms of Cytochrome P450 1B1 (Val432Leu CYP1B1), Phenol-sulfotransferase 1A1 (Arg213His SULT1A1) and Catechol-O-methyltransferase (Val158Met COMT). The smokers carrying the Val CYP1B1 allele associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 36 publications
0
52
1
3
Order By: Relevance
“…The inconsistency between these studies may show the variability of other genetic and environmental factors linked to CYP1B1 expression and metabolism during breast carcinogenesis in different populations. These could include but are certainly not limited to body mass index (129), catechol-O-methyltransferase status (131), CYP1A1 status (43), ER status (124), having undergone menopause, and exposure to environmental carcinogens (137).…”
Section: Mol Cancer Res 2006;4(3) March 2006mentioning
confidence: 99%
See 2 more Smart Citations
“…The inconsistency between these studies may show the variability of other genetic and environmental factors linked to CYP1B1 expression and metabolism during breast carcinogenesis in different populations. These could include but are certainly not limited to body mass index (129), catechol-O-methyltransferase status (131), CYP1A1 status (43), ER status (124), having undergone menopause, and exposure to environmental carcinogens (137).…”
Section: Mol Cancer Res 2006;4(3) March 2006mentioning
confidence: 99%
“…Such studies have found that smoking confers a further increase in breast cancer risk in individuals with the CYP1B1*3/*3 genotype (137). A prevailing hypothesis is that CYP1B1 is transcriptionally induced by polyaromatic hydrocarbons and other aromatic hydrocarbons (major constituents of cigarette smoke) resulting in increased levels of CYP1B1.…”
Section: Mol Cancer Res 2006;4(3) March 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…Some rather small previous studies (103-444 cases) involving different ethnic study populations that have explored the potential association between the SULT1A1 c.779G>A polymorphism and breast cancer risk have shown inconsistent results (6)(7)(8)(9). A number of studies with conflicting outcomes have also been conducted on SULT1A1 c.779G>A polymorphism and cancers of lung, colon, prostate, bladder, esophagus, and urinary tract (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic polymorphisms that influence expression and activity have been identified for all five of these enzymes. However, only genetic polymorphisms in CYP1A1 and CYP1B1 have been studied in association with breast cancer risk to date (53)(54)(55)(56)(57)(58)(59)(60)(61), with conflicting results.…”
Section: Discussionmentioning
confidence: 99%